STRENGTHENING STUDENTS' RELIGIOUS CHARACTER EDUCATION THROUGH ISLAMIC BEHAVIOR HABITUATION PROGRAM MANAGEMENT - Umi Afifah; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the concept of Islamic education management in developing students' religious character and to construct a conceptual framework for implementing Islamic behavioral habituation programs. The study employed a qualitative approach using a descriptive-analytical literature review method through content analysis technique. The findings indicate that the management of Islamic behavioral habituation programs requires a holistic, systematic, and integrative approach grounded in the integration of three main pillars: Islamic education management theory, behavioristic learning theory, and character education theory, oriented toward the tarbiyah goal of forming the insan kamil — a complete human being encompassing the dimensions of aqidah, ibadah, and akhlak. Operationally, the strengthening of religious character is carried out through the POAC management functions and five key strategies, namely curricular integration, modeling, the creation of a religious school culture, parental collaboration, and the reinforcement of students' intrinsic motivation. The conceptual framework for implementation comprises five components: an Islamic philosophical foundation, a periodically structured program design, leadership- and modeling-based implementation, institutional system support, and continuous evaluation encompassing cognitive, affective, and psychomotor aspects. The resulting conceptual framework is adaptive to the diverse contexts of schools across Indonesia and serves as a practical reference for designing Islamic behavioral habituation programs that are systematic, measurable, and effective.